Psychological Reflections in the Philosopher’s Mirror: Comments on Thomas Kelly’s Bias: A Philosophical Study - Celniker, Jared B. (International journal for the study of skepticism, 2024)
In this brief commentary, we offer thoughts on Thomas Kelly’s Bias: A Philosophical Study. We focus on the book’s relevance to the study of cognitive biases, including Kelly’s discussion of naïve realism (in the psychologists’ sense). While we are largely enthusiastic about Kelly’s theorizing, we also provide some pushback against his notion of emergent biases. We hope that psychologists will engage with Kelly’s work and might consider how some philosophical refinements could improve the empirical study of biases.